Nutritional status and associated factors in under-five children in Lembar Village West Lombok, Indonesia - Widya Dwijayanti; Dewa Nyoman Wirawan; Luh Seri Ani; Ni Wayan Arya Utami (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: Studies on determinants of nutritional status in under-five children in Indonesia have been widely explored. However, most studies utilised only one out of three nutritional status indicators–weight/age, height/age, or weight/height. These studies also show inconsistent results. This present study aims to examine nutritional status in under-five children by using all three indicators and associated factors which include mother’s characteristics, nutrition intake, and child’s history of infectious diseases. Methods: A cross-sectional study was conducted with a total sample of 100 under-five children who were randomly selected. Data on the mother’s characteristics, nutrition intake, and child’s history of infectious diseases were collected through structured interview with the mother, while data on nutritional status were obtained through measurements. Data were analysed using logistic regression to identify association between the nutritional status of under-five children with the mother’s characteristics, nutrition intake, and child’s history of infectious diseases. Results: There was no association between the nutritional status of under-five children based on weight/age, height/age, and weight/ height with the mother’s characteristics and nutrition intake. However, there was an association between the nutritional status of under-five children and child’s history of infectious diseases with an adjusted odd ratio (AOR)=41.0 (95% CI: 12.10-139.14) for weight/age, AOR=3.52 (95%CI: 1.53-8.05) for height/age, and AOR=10.69 (95%CI: 1.31-87.11) for weight/height. Conclusions: Child’s history of infectious diseases is the only determinant associated with nutritional status in under-five children based on weight/ age, height/age, and weight/height. Prevention measures are required to prevent infection among children by improving environmental hygiene as well as providing prompt treatment for infectious diseases especially diarrhoea and upper-respiratory tract infection.